(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Acne vulgaris is a chronic, inflammatory disease of the pilosebaceous unit. Acne is a skin disorder associated with multifactorial pathogenesis. Obestatin and ghrelin are largely produced throughout the GI tract (e.g., stomach, pancreas and duodenum) with predominant expression in the gastric mucosa. Ghrelin produced in deep hair follicles and sebaceous glands may fold pathogenesis of acne vulgaris and cause acne in humans. Aim The aim of this study is to evaluate serum level of Ghrelin and Obestatin in Acne Vulgaris patients and to correlate between level of Ghrelin and Obestatin and disease severity. Patients and Methods The study is a prospective case control study that was conducted on patients with acne vulgaris aged between 15-30 years. Forty patients (15males and 25 females) with acne vulgaris and forty normal healthy control (21 males and 19 females) who matched the cases group as regard age and sex were included in this work. They were selected from the Dermatology Outpatient Clinic, Mansoura University Hospital. Results Serum ghrelin was significantly lower in the Acne Vulgaris group with mean ±SD (585.98 ±21.08) when compared to the control group with mean± SD (1139.2 ± 84.22), p<0.001. Serum obestatin was non significantly lower in Acne Vulgaris group with mean± SD (202.5 ± 14.72) when compared to the control group with mean ± SD (265.7± 33.14), p>0.05. Serum ghrelin decreased significantly with increased severity (p<0.001). Serum obestatin decreased non significantly with increased severity (p>0.05). Serum ghrelin showed significant positive correlation with serum obestatin among all studied patients. Conclusion serum ghrelin and obestatin levels desreased in acne vulgaris patients and serum ghrelin showed significant negative correlation with severity.